A systematic literature review on combined seawater desalination and reverse electrodialysis: Evaluating its technological readiness and potential for full-commercialization - Marijn T. van Geet; Janina Fuchs (Energy Nexus)
Combined seawater desalination and reverse electrodialysis technology has emerged as an eco-innovation that holds great promise to enhance the economic and environmental performance of the desalination industry. However, despite its apparent benefits and increased academic interest, reverse electrodialysis is, to date, not commonly used in combination with desalination. Using a technological readiness perspective, the current study evaluates its technological maturity and potential to achieve full commercialization. Based on a structured literature review including 70 recent publications on the topic, the current study identified four main techno-economic barriers that stand in the way of this eco-innovation progressing to wide-scale adoption: (1) a low power density and energy efficiency; (2) a high levelized cost of energy; (3) technological immaturity; and (4) a lack of competitiveness. The technological immaturity of combined seawater desalination and reverse electrodialysis technology is one of the prime reasons for the low power density and energy efficiency, which in turn has a causal relationship with the high costs associated with the technology. Additionally, the high costs may contribute to the lack of competitiveness. It is concluded that these main barriers might cause the eco-innovation to fall victim to the so-called ''Valley of Death,'' a funding gap between the proof of concept within academia and the adoption of the technology by the industry on a commercial scale. These findings have implications for future policy initiatives and investment decisions that aim to decarbonize and lessen the desalination industry's environmental impact.